Sequence Assembly with CAFTOOLS - Dear, Simon; Durbin, Richard; Hillier, LaDeana; Marth, Gabor; Thierry-Mieg, Jean; Mott, Richard (Genome Research, 1998)
Large-scale genomic sequencing requires a software infrastructure to support and integrate applications that are not directly compatible. We describe a suite of software tools built around the Common Assembly Format (CAF), a comprehensive representation of a sequence assembly as a text file. These tools form the backbone of sequencing informatics at the Sanger Centre and the Genome Sequencing Center. The CAF format is intentionally flexible, and our Perl and C libraries, which parse and manipulate it, provide powerful tools for creating new applications as well as wrappers to incorporate other software. The tools are available free by anonymous FTP from ftp://ftp.sanger.ac.uk/pub/badger/.